Rural medicine and ‘home stay’: a medical student’s experience - Reabetswe Ntshabele; Rubeshan Perumal; Nesri Padayatchi (South African Family Practice)
Medical education is evolving from a heavily hierarchical and paternalistic approach to a more developmental and student-centred paradigm. In addition, there has been a greater focus on decentralised medical education, taking medical students closer to the lowest tiers of the healthcare system and allowing for a more immersive experience within the communities of their patients. This paper presents the experience of an enlightening rural experience, in which the benefits of such a model to medical education are explored. Furthermore, it presents the highly personal and developmental journey that decentralised and, in particular, rural medical training can offer. A new concept of a ‘home-stay’ model has now been introduced as part of the rural medicine experience, where students are hosted by a family within the community in which they work. This is a transformative project in which the most fundamental principles of medical training and the art of medical practice can be honed. The convergence of clinical training, public health enlightenment, and family practice are highlighted.